Nucleotide sequence of a cluster of early and late genes in a conserved segment of the vaccinia virus genome. - Plucienniczak, A (1985)
The nucleotide sequence of a 7.6 kb vaccinia DNA segment from a genomic region conserved among different orthopox virus has been determined. This segment contains a tight cluster of 12 partly overlapping open reading frames most of which can be correlated with previously identified early and late proteins and mRNAs. Regulatory signals used by vaccinia virus have been studied. Presumptive promoter regions are rich in A, T and carry the consensus sequences TATA and AATAA spaced at 20-24 base pairs. Tandem repeats of a CTATTC consensus sequence are proposed to be involved in the termination of early transcription.